Isolation and characterization of antimutagenic components of Glycyrrhiza aspera against N-methyl-N-nitrosourea. (December 2017) - Inami, Keiko; Mine, Yusuke; Tatsuzaki, Jin; Mori, Chihiro; Mochizuki, Masataka
Abstract Background A powdered ethanolic extract ofGlycyrrhiza aspera root exhibits antimutagenic activity againstN -methyl-N -nitrosourea (MNU) based on the Ames assay withSalmonella typhimurium TA1535. The aim of this study was to identify the antimutagenic components of the powdered ethanolic extract ofG. aspera root. Results The powdered ethanolic extract ofG. aspera root was sequentially suspended inn -hexane, carbon tetrachloride, dichloromethane, ethyl acetate, and ethanol, and each solvent soluble fraction and the residue were assayed for antimutagenic activity against MNU inS. typhimurium TA1535. The dichloromethane soluble fraction exhibited the highest antimutagenicity and was fractionated several times by silica gel chromatography. The fraction with the highest antimutagenic activity was further purified using HPLC, and the fractions were assayed for antimutagenicity against MNU inS. typhimurium TA1535. Finally, five components with antimutagenic activity against MNU were identified as glyurallin A, glyasperin B, licoricidin, 1-methoxyphaseollin, and licoisoflavone B. Conclusions The five components were demonstrated to possess an antigenotoxic effect against carcinogenic MNU for the first time. It is important to prevent DNA damage byN -nitrosamines for cancer chemoprevention.